DESAIN MODEL FUZZY-TSUKAMOTO UNTUK PENENTUAN KUALITAS BUAH PEPAYA CALIFORNIA (CARICA PAPAYA L.) BERDASARKAN BENTUK FISIK - Al Rivan, Muhammad Ezar; Octavia, Angella; Wijaya, Irvan (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
Papaya easily found in the local market with a relatively cheap price, adequate nutrient and vitamin content. The quality of California papaya can be measured by size, color and defect. This research discusses the topic of fuzzy model design regarding the measured of the quality of papaya using fuzzy tsukamoto with input variables major axis, minor axis, red and green intensity color, and defect variables along with the output as a result of determining the quality of California papaya. Based on the tests that have been carried out, the results of the quality is 75%.